2018
DOI: 10.1111/auar.12251
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Mutual Understanding Between External Accountants and Owner–Managers of SMEs

Abstract: This study investigates the perspective of the owner–manager of a small or medium‐sized enterprise (SME) on the importance of mutual understanding with an external accountant. Mutual understanding means that the owner–manager understands what the accountant is saying and feels understood by the accountant. The results, based on 310 completed surveys of Belgian owner–managers, show that owner–managers who have a high level of mutual understanding use the advice of their external accountant more extensively. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
2
24
0
4
Order By: Relevance
“…The results thus confirmed that the advice of an accountant truly supports entrepreneurs to carefully consider and analyze the diverse subjects of the business plan. This finding is in line with previous research that stresses the increasingly important advisory and educational role of the accountant [79,97,117]. In order to benefit from the information captured in a business plan, entrepreneurs need to thoroughly understand its dynamics [23,27].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results thus confirmed that the advice of an accountant truly supports entrepreneurs to carefully consider and analyze the diverse subjects of the business plan. This finding is in line with previous research that stresses the increasingly important advisory and educational role of the accountant [79,97,117]. In order to benefit from the information captured in a business plan, entrepreneurs need to thoroughly understand its dynamics [23,27].…”
Section: Discussionsupporting
confidence: 87%
“…During the business planning stage, accountants transcend their traditional role, in which they offer support to comply with legal requirements. However, in line with previous research focusing on the role of external accountants as business advisers [97,117], it seems that their service provision during the planning stage is not exploited to its full extent. External accountants guide their client entrepreneurs during the development of a business plan and the actual launch of a business.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…De Bruyckere et al. (2020) explore the nature of the relationship between the owner‐managers of SMEs and the external accountant. The greater the understanding between the owner‐manager and their external accountant, the more likely it is that advice from the accountant is followed.…”
mentioning
confidence: 99%